Intervensi Sosial Pada Mahasiswa Psikologi Universitas Bhayangkara Jakarta Raya yang Mengalami Stress Akademik - Afsari, Tri; Wijaya, Caroline Maryam; Rossianah, Intan; Kamal, Muhammad Fathul; Chelsea, Latifa Naira; Abdillah, Rijal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Students often face various challenges in higher education, such as intense academic demands and changes in the learning system. This often triggers academic stress that negatively impacts mental health, productivity and overall well-being. This study aims to identify the level of academic stress, analyze its impact on Psychology students of Bhayangkara University of Greater Jakarta, and design a psychoeducation-based social intervention program. The methods used provision of psychoeducation through posters and brochures. The intervention results showed that students experienced academic stress due to internal and external factors, such as time, social support, and academic demands. The intervention program succeeded in increasing students' understanding of academic stress and how to manage it. With the implementation of this intervention, students are expected to cope with academic stress more effectively and improve their well-being.